Barriers to men's participation in perinatal care: a qualitative study in Iran - Vahideh Firouzan; Mahnaz Noroozi; Ziba Farajzadegan; Mojgan Mirghafourvand (BMC, 2019)
Abstract Background The role of men's participation in prenatal, delivery and postpartum care is very important, well defined and cannot be over emphasized. Very few studies exist about men's role in promoting the health of the mother and barriers to their participation in perinatal care in Iran; hence, the present study was conducted to determine the barriers to men's participation in perinatal care. Methods The present qualitative study was carried out on 45 participants who were selected employing purposeful sampling technique. Data were collected through in-depth semi-structured interviews, focused group discussions and field notes. Data were analyzed using conventional content analysis. Results After data analysis, four main categories extracted were: "cultural barriers", "personal and interpersonal barriers", "health system-related barriers" and "socio-economic barriers". Conclusion The results of this study, by presenting the barriers to and challenges for men's participation in perinatal care, could be helpful in designing culture-based strategies to overcome these barriers and improve men's participation.